P5.085 Treponema Pallidum Antibodies Detection by a Point-Of-Care Test and RPR and TPHA Tests in MSM Attending a Community Based HIV Anonymous Center - Checkpoint LX. (13th July 2013) - Castro, R; Lopes, Â; Fuertes, R; Machado, H; Rocha, M; Jordão, R; Brito, J; Esteves, J; Campos, M J; Pereira, F
Abstract : Background: When available, point-of-care tests are very useful in the screening of STIs. They have affordable prices, need minimal equipment and training, results are immediately available, allowing treatment with no delay. Objectives: We describe the prevalence of syphilis in an MSM population attending an HIV Anonymous Testing Center (ATC), who stated that they were never infected with Treponema pallidum, as evaluated with a rapid test. Positive results were confirmed with the RPR and TPHA tests. Materials and Methods: Nine hundred and forty four individuals attending the HIV ATC were tested with the Determine Syphilis TP test. Those who were found to have reactive results had blood taken for confirmation with RPR and TPHA tests. Results: The rapid test was reactive in 44 of the 944 (4.7%) individuals. Samples were further tested with the RPR and the TPHA tests; 34 showed to have antibodies against T. pallidum in both tests, although one sample was reactive only at the 1:2 dilution in the RPR and its TPHA titer was 1:640. Six samples were only reactive for the TPHA test, while four were non reactive in both tests. The FTA-ABS was performed in these four samples and it was non reactive. Discussion: and conclusion: In accordance with the results of the rapid test, the percentage of reactive samples was 4.7% (44/944). However, when confirmatory tests were performed in the samples received in the laboratory, the percentage of reactive samples decreased to 4.2% (40/944). Furthermore, in six of these samples only the TPHA was reactive, meaning that these patients probably had a treated past infection, which was not detected as such by the rapid test. In conclusion, the Determine Syphilis TP test seems to be useful as a screening test for syphilis, although it does not differentiate between treated and active syphilis.